Control design of Modular Multilevel Converters in normal and ACfault conditions for HVDC grids - Prieto-Araujo,E; Junyent,Ferre A; Collados-Rodríguez,C; Clariana-Colet,G; Gomis-Bellmunt,O (Electric Power Systems Research, 2017)
This paper describes a control design strategy of Modular Multilevel Converters (MMC) for High Voltage Direct Current (HVDC) applications to operate during normal and AC fault conditions. First, a steady state analysis of the converter is performed to identify the uses of the current components within the control strategy. Based on the initial stationary study, a complete converter control structure is proposed, which enables full control of the MMC internal energy during normal and AC fault conditions. A detailed design procedure is included for the current and energy regulators, in order to be able to ensure a dynamic response under any grid condition. Finally, theoretical developments are validated through simulation results by means of a detailed model in normal operation and during an AC voltage sag.